Proposing Some New Ecliptics in New Testament Studies Enabled by Digital Humanities-Based Methods - Libby, James A. (Journal of religion, media and digital culture, 2016)
“Fragmentation” is a well-worn watchword in contemporary biblical studies. But is endless fragmentation across the traditional domains of epistemology, methodology and hermeneutics the inevitable future for the postmodern exercise of biblical scholarship? In our view, multiple factors mitigate against such a future, but two command our attention here. First, digital humanities itself, through its principled use of corpora, databases and computer-based methods, seems to be remarkably capable of producing findings with high levels of face validity (interpretive agreement) across multiple hermeneutical perspectives and communities. Second, and perhaps more subversively, there is a substantial body of practitioners that, per Kearney, actively question postmodernity’s impress as the final port of call for philosophy. For these practitioners deconstruction has become both indispensable — by delegitimizing hegemonies — but, in its own way, metanarratival by stultifying all other iterative, dialectical and critical processes that have historically motivated scholarship. Sensing this impasse, Kearney (1987, pp. 43-45) proposes a reimagining that is not only critical but that also embraces ποίησις, the possibility of optimistic, creative work. Such a stance within digital humanities would affirm that poietic events emerge not only through frictions and fragmentation (e.g. Kinder and McPherson 2014, pp. xiii-xviii) but also through commonalties and convergence. Our approach here will be to demonstrate such a reimagining, rather than to argue for it, using two worked examples in the Greek New Testament (GNT). Those examples - digital humanities-enabled papyrology and digital humanities-enabled statistical linguistics - demonstrate ways in which the data of the text itself can be used to interrogate our perspectives and suggest that our perspectives must remain ever open to such inquiries. We conclude with a call for digital humanities to further leverage its notable strengths to cast new light on old problems not only in biblical studies, but across the spectrum of the humanities.